Interleukins 30 and 27 in psoriasis and inflammation - Majchrzycka, Marianna; Wegner, Joanna; Adamski, Zygmunt; Jenerowicz, Dorota (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
This review explores the roles of interleukin-30 (IL-30) and interleukin-27 (IL-27) in inflammation and autoimmune diseases, with a focus on psoriasis. The two coexisting cytokines should be analysed in conjunction as their actions are antagonistic in vivo. While IL-27 exhibits diverse anti-inflammatory mechanisms, the understanding of IL-30’s functions remains limited. Studies suggest that IL-27 may play a role in regulating psoriasis, but findings are inconsistent. IL-30 shows promise in mitigating psoriatic lesions and suppressing inflammatory responses. However, research on IL-30’s involvement in autoimmune diseases presents conflicting results. This article provides a literature review on the complex correlations between cytokines, their role in the pathogenesis of psoriasis, inflammation, carcinogenesis, and autoimmune diseases, and provides a detailed picture of the interplay between IL-27 and IL-30 to uncover novel therapeutic targets for psoriasis and other autoimmune conditions.